2020
DOI: 10.5603/pjnns.a2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous and sinus thrombosis diagnosis: preliminary study of clinical picture and D-dimer concentration correlation

Abstract: Aim of the study. We investigated whether D-dimer (DD) concentration is elevated in cerebral venous and sinus thrombosis (CVST), as has been reported in the literature. Clinical rationale for the study. CVST is a disease with variable clinical presentations and a challenging diagnosis. We looked into whether D-dimer concentration might be an indicator of CVST, and the need for neuroimaging tests correlated with clinical factors. Materials and methods. We included all consecutive patients (mean age 41.6 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…D-dimer is one of the important indicators for CVT diagnosis. [21][22][23][24] However, in our study, the level of D-dimer was not associated with the presence of CVT in patients with DAVF. The result is consistent with a small study including 18 patients with DAVF, which showed no significant difference between the mean value of D-dimer and sinus occlusion.…”
Section: Discussioncontrasting
confidence: 80%
“…D-dimer is one of the important indicators for CVT diagnosis. [21][22][23][24] However, in our study, the level of D-dimer was not associated with the presence of CVT in patients with DAVF. The result is consistent with a small study including 18 patients with DAVF, which showed no significant difference between the mean value of D-dimer and sinus occlusion.…”
Section: Discussioncontrasting
confidence: 80%
“…It should be noted that although the use of Ddimer testing has been well established in ruling out the venous thromboembolism, such as pulmonary embolism and deep vein thrombosis, the usefulness of which is still debatable in CVT, with an unacceptable false-negative rate of up to 26%. Nevertheless, positive D-dimer strengthens the suspicion of CVT in patients with acute headache (23,(58)(59)(60)(61)(62)(63).…”
Section: Cerebral Angiographymentioning
confidence: 97%
“…Cerebral venous and sinus thrombosis (CVST) is another disease where headache is the predominant symptom. As with SuS, it affects typically young adults, mainly females, which can lead to misdiagnosis [41]. CVST has a lot of varying clinical manifestations similar to SuS, but it is important to remember that the treatment differs significantly.…”
Section: Differential Diagnosismentioning
confidence: 99%